Dynamic Regulation of the GABAA Receptor Function by Redox Mechanisms - Calvo, Daniel Juan (2016)
Oxidizing and reducing agents, which are currently involved in cell metabolism and signaling pathways, can regulate fast inhibitory neurotransmission mediated by γ-aminobutyric acid (GABA) receptors in the nervous system. A number of in vitro studies have shown that diverse redox compounds, including redox metabolites and reactive oxygen and nitrogen species, modulate phasic and tonic responses mediated by neuronal GABAA receptors through both pre- and postsynaptic mechanisms. We review experimental data showing that many redox agents, which are normally present in neurons and glia or are endogenously generated in these cells under physiological states or during oxidative stress (e.g: hydrogen peroxide, superoxide and hydroxyl radicals, nitric oxide, ascorbic acid, glutathione), induce potentiating or inhibiting actions on different native and recombinant GABAA receptor subtypes. Based on these results, it is thought that redox signaling might represent a homeostatic mechanism that regulates the function of synaptic and extrasynaptic GABAA receptors in physiological and pathological conditions.